2013
DOI: 10.3109/08958378.2013.764946
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of adult and senescent Brown Norway rats to repeated ozone exposure: an assessment of behavior, serum biochemistry and cardiopulmonary function

Abstract: Ozone (O₃) is a pervasive air pollutant that produces pulmonary and cardiovascular dysfunction and possible neurological dysfunction. Young and old individuals are recognized as being susceptible to O₃; however, remarkably little is known about susceptibility with senescence. This study explored the pulmonary, cardiovascular and neurological effects of O₃ exposure in adult (4 m) and senescent (20 m) Brown Norway rats exposed to 0 or 0.8 ppm O₃ for 6 h, 1 d/week, for 17 weeks. Ventilatory function was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…A recent study from this laboratory reported on respiratory, cardiovascular and serum biomarker responses of 4-, 12-and 24-month-old rats subjected to subchronic O 3 exposure (0.8 ppm, 1 d/week for 16 weeks; Gordon et al, 2013). The effects of O 3 on respiratory mechanics evaluated in a sealed chamber (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from this laboratory reported on respiratory, cardiovascular and serum biomarker responses of 4-, 12-and 24-month-old rats subjected to subchronic O 3 exposure (0.8 ppm, 1 d/week for 16 weeks; Gordon et al, 2013). The effects of O 3 on respiratory mechanics evaluated in a sealed chamber (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots of BALF were used to determine total cell counts with a Z1 Coulter Counter (Coulter, Inc., Miami, FL) and cell differentials according to previously described procedures (Gordon et al, 2013). The cell free BALF was used to analyze lung injury biomarkers [total protein, albumin lactate dehydrogenase (LDH) activity, N-acetyl glucosaminidase (NAG) activity and γ-glutamyl transferase (GGT)] activity as described earlier (Gordon et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…A proprietary algorithm within the software automatically pre-screens measurements for acceptability, and rejects values falling outside of a pre-programmed range. Components of the plethysmography system and its operation are described elsewhere (Gordon et al, 2013;Hamelmann et al, 1997;Shannahan et al, 2010) and are unchanged from previous studies, with the exception of the N-O plethysmographs, which we had not previously utilized. The N-O plethysmographs were used following the manufacturer's instructions, with the exception that the pneumotachometers, which convert air flow in the plethysmograph into quantifiable signals representing changes in air pressure, were moved from the cone's rear sidewall to the back of the rear plunger (similar to N-O plethysmographs for mice), to prevent interference with the screen by fur or dander.…”
Section: Plethysmograph Exposure System (Experiments 2)mentioning
confidence: 98%